Letter (copy)
012a-0047-001 Secretary's. HVT/FC. The Opera House, Winter Gardens, Blackpool Mr. J. M. Batista i Roca The Queen Hydro Hotel, BLACKPOOL. 7th September, 1938. Dear Sir, I thank you for your letter of the 6th instant. I am afraid it will not be possible for Sir Walter Citrine to see you, but if you will call at our office at the Opera House, Winter Gardens, at 12 noon to-morrow, Thursday, I shall be pleased to see you. Yours faithfully. General Secretary. 292/946/12a/47